Efek antibakteri dan penghambatan biofilm ekstrak sereh (Cymbopogon nardus L.) terhadap bakteri Streptococcus mutans - Zwista Yulia Dewi; Asikin Nur; Triana Hertriani (Faculty of Dentistry, Universitas Gadjah Mada, 2015)
Antibacterial effect and biofilm inhibition Of Lemongrass extract (Cymbopogon nardus L.) against the growth of Streptococcus mutans. Caries prevention can be carried out by several methods. One of them is by controlling the plaque accumulation on the surface of the teeth. Lemongrass (Cymbopogon nardus L) is containing certain compound that can inhibit the growth of bacteria and biofilm. The objective of this research is to observe the influence of antibacterial and biofilm inhibition of lemongrass extract against the growth of S. mutans. Subjects were S. mutans bacteria on KHM90 test as much as 6x108 CFU/ml and on biofilm inhibition test as much as 15x108 CFU/ml. Lemongrass was extracted using petroleum ether followed by using 70% ethanol. Antibacterial activity test carried out with KHM90 determination test using microdilution method on microplate flat bottom 96 wells. Bacteria were prepared by making a suspension in NB media and adjusted to McFarland II standard (6x108 CFU/ml). Biofilm inhibition activity test was performed using microdilution method of the biofilm formed on microplate flat flexible PVC U-bottom 96 wells which were stained using 1% of crystal violet. Bacteria were prepared by making a suspension in BHI media and adjusted to McFarland V standard (15 x108 CFU/ml). The result in the form of optical density (OD) was read by Bio-rad microplate reader Benchmark at a wavelength of 595 nm. The value of IC50 was determined by probit method using SPSS version 15.The results of this study of measurements on KHM90 test showed that 108,36% w/v is capable of inhibiting the growth of bacteria. Biofilm inhibitory activity showed IC50 lemongrass value was 0,137% w/v. The conclusion of this study is that lemongrass extract has antibacterial effect against bacteria S. mutans showed by KHM90 obtained at concentrations of 0,18% w/v and there is lemongrass extract biofilm inhibitory effect against the bacteria S. mutans indicated by IC50 value 0,137%